Preterm birth and subsequent insulin sensitivity: a systematic review. Issue 4 (20th December 2013) - Tinnion, Robert; Gillone, Jenna; Cheetham, Timothy; Embleton, Nicholas
Abstract : Objective: The incidence of preterm birth is increasing worldwide. Evidence suggests that in later life these children are at increased risk of 'metabolic syndrome', which is itself associated with reduced insulin sensitivity (IS). We carried out a systematic review to examine whether preterm birth is associated with later changes in IS and whether a difference exists between those born small-for-gestational age (SGA) and appropriate-for-gestational age (AGA). Methods: We used the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidance to structure our review with a priori data extraction criteria to answer the questions posed and then carried out our literature search. Only papers which included preterm infants in their study population and specifically assessed IS were included. Findings are reported by age group to enable change over the life course to be examined, even though the studies were mostly cross-sectional, observation studies. Results: We identified and reviewed 26 suitable publications representing 20 separate cohorts, of which 16 had a term control group. The heterogeneity of the methods used to measure IS precluded meta-analysis. In infancy and early childhood there is a measurable association between IS and preterm birth. In later childhood and adulthood the strength of this association reduces, and current body composition becomes the variable most strongly associated with IS. Conclusions: There is an association between preterm birth and IS throughout the life course, but the data are conflicting and associations are likely to be affected by the heterogeneity of each study population and multiple confounding factors that may change over time. While the optimal nutritional strategy for preterm infants remains to be determined, standard public health guidance to avoid obesogenic lifestyle factors remains equally important to individuals born preterm.